Age differences in option choice: Is the option framing effect observed among older adults? - Masumoto, Kouhei; Tian, Min; Yamamoto, Kenta (Frontiers in Psychology, 2022)
Previous studies reported that consumers choose a higher number of options in subtractive framing (−OF), which delete the unnecessary options from the full model with all options chosen than in additive framing (+OF), which adds options to a simple base model. The purposes of this study are to examine the effect of age on option framing and the differences of product type on the option framing effect using two product scenarios (travel package and medical examination). Participants were 40 younger and 40 older adults. We measured the number of options chosen, total price, choice difficulty, and choice satisfaction. In addition, cognitive functions (coding, symbol search, digit span, arithmetic, and information) were assessed. Results revealed that older and younger adults chose more options in the −OF condition for both the scenarios. For the medical examination, older adults chose more options than did the younger adults in both −OF and +OF conditions. Developmental shift in goals and motivation related to life-span may explain the differences between the age differences.